2016
DOI: 10.1371/journal.pone.0167508
|View full text |Cite
|
Sign up to set email alerts
|

Dengue and Chikungunya Virus Infections among Young Febrile Adults Evaluated for Acute HIV-1 Infection in Coastal Kenya

Abstract: BackgroundFever is common among patients seeking care in sub-Saharan Africa (sSA), but causes other than malaria are rarely diagnosed. We assessed dengue and chikungunya virus infections among young febrile adults evaluated for acute HIV infection (AHI) and malaria in coastal Kenya.MethodsWe tested plasma samples obtained in a cross-sectional study from febrile adult patients aged 18–35 years evaluated for AHI and malaria at urgent care seeking at seven health facilities in coastal Kenya in 2014–2015. Dengue v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The results obtained may be due to the fact that the majority of the participants included in the analysis were asymptomatic. This is in accordance with results observed in other studies [16, 20, 21]. During epidemics, all these pathologies are clinically difficult to distinguish from other diseases, and differential diagnosis in case of suspicion remains a major problem to date [22, 23].…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained may be due to the fact that the majority of the participants included in the analysis were asymptomatic. This is in accordance with results observed in other studies [16, 20, 21]. During epidemics, all these pathologies are clinically difficult to distinguish from other diseases, and differential diagnosis in case of suspicion remains a major problem to date [22, 23].…”
Section: Discussionsupporting
confidence: 91%
“…In 2013, an outbreak of DENV-2 in Mombasa was detected, in part, by RT-PCR ( 7 ). More recently, DENV infections were described in 43 adult patients with fever who resided in Mtwapa, on the coast of Kenya near Mombasa; these cases occurred February 2014–January 2015 ( 8 ), which overlapped with the period in which we observed the DENV cases we report in this study. All of the DENV PCR-positive subjects from the 2016 study were infected with DENV-2, which is consistent with the DENV serotype observed in the 2013 Mombasa outbreak ( 7 ).…”
supporting
confidence: 59%
“…The virus causes variable symptoms ranging from mild febrile illness to the more severe dengue hemorrhagic fever, which can progress to a fatal form, dengue shock syndrome (DSS). Aedes aegyptii and Aedes albopictus are the two competent vectors of the virus worldwide [ 59 , 60 , 61 ]; hence, Culex mosquitoes ingested the virus from viremic hosts. The Kenyan coastal towns, which include Kwale, have experienced intermittent outbreaks due to dengue 2 in the past and presence of the virus suggests continuous low-level circulation.…”
Section: Discussionmentioning
confidence: 99%